(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Rootlessness, displacement and the longing for self are prominent traits of the modern world. Africa having been gouged open by colonialism is not exempted from waves of these vices. In fact, postindependence Africa is overwhelmed by its multitude citizens who have caught the fever of migration and are eager and willing to undergo the arduous task of relocating to the West in order to escape the maze of socio-political and economic pitfalls sinking their home countries. Due to the barrage of these intercontinental movements, the world is shrunk into a global-cultural village, as indigenous cultures are dislocated and made to collide with Western cultures to yield cultural amalgams. Hence, this discourse, by deploying postcolonialism as its framework and critical textual analysis as its method, aims to analyse the postcolonial tenets of migration, hybridity and identity in Chimamanda Ngozi Adichie’s Americanah. The study unearths that African citizens are constantly migrating to the West to seek better living conditions, and on getting there oftentimes discover, albeit disappointedly, that the grass may not always be greener abroad as they have to settle for menial jobs and are plunged into a host of immigrant insecurities like survival tussles, cultural alienation, identity rift, racial bigotry, et cetera. The essay concludes that Africa’s political elite have to awaken from their slumber to develop their continent in order to curb the menace of migration and also Africans must continue to assert their culture in a world overridden by Westernisation.